2013
DOI: 10.1016/j.leukres.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Abducted by the illness: A qualitative study of traumatic stress in individuals with acute leukemia

Abstract: Symptoms of traumatic stress are common in acute leukemia. The goal of the present qualitative study was to understand this traumatic stress, as perceived by patients. Participants were 43 patients with acute leukemia in Toronto, Canada. Participants were asked in serial interviews about their experience of diagnosis and treatment. A total of 65 interviews were analyzed utilizing the grounded theory method. Our findings provide insight into the traumatic experience of the diagnosis and treatment, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 35 publications
(44 reference statements)
5
70
1
Order By: Relevance
“…http Other studies have suggested that a significant proportion of AML patients suffer from ongoing fatigue and one-third had significant depressive symptoms [19]; emotional, role, and social function remain impaired 12 months after diagnosis [20]. A qualitative study suggested that a diagnosis of AML is associated with significant psychological distress [21,22]. Qualitative studies with patients with various hematological malignancies including AML undergoing hematopoietic stem cell transplantation have identified a state of fluctuation between fear and hope which extended from diagnosis to recovery phases [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…http Other studies have suggested that a significant proportion of AML patients suffer from ongoing fatigue and one-third had significant depressive symptoms [19]; emotional, role, and social function remain impaired 12 months after diagnosis [20]. A qualitative study suggested that a diagnosis of AML is associated with significant psychological distress [21,22]. Qualitative studies with patients with various hematological malignancies including AML undergoing hematopoietic stem cell transplantation have identified a state of fluctuation between fear and hope which extended from diagnosis to recovery phases [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Knowing this could help health care professionals (HCPs) such as doctors and nurses better prepare newly diagnosed patients. Additionally, despite the influence of age on disease biology and response to treatment, age-related differences in recovery have not been addressed to date [21,22]. Therefore, the purpose of this study was to explore the survivorship issues encountered by AML survivors 6 months after diagnosis and who had just completed successfully IC, and explore if these survivorship issues are different for younger and older survivors.…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting findings in the initial phase of leukemia diagnosis and treatment showed that recently diagnosed patients and those undertaking treatment preferred to surrender control to health care providers [7,9]. While the important role of empowering patients has been emphasized in literature on adaptation to cancer [31], relinquishing control has been identified as an adaptive response in highly stressful and unknown situations [9]. Given the current inconsistent evidence and the significant role of perceived control in stress, coping, and adaptation [32], further investigation is warranted to identify personal and situational factors contributing to adaptive use of control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, two recent cross-sectional studies on newly diagnosed AML patients receiving IC and one longitudinal study of AML patients undergoing prolonged chemotherapy documented a high prevalence of traumatic stress symptoms, intense worrying and sadness, uncertainty about durable remission, and fear of cancer recurrence as serious threat to psychological well-being [4,5,8]. Correspondingly, several qualitative studies investigating patients' perspectives on the initial phase of leukemia diagnosis, IC, and bone marrow transplantation (BMT) noted a sense of shock, emotional numbness, threat, insecurity, uncertainty, and fear regarding diagnosis, invasive procedures, cancer recurrence, and transplant rejection [9][10][11][12]. Although data from the initial phase of leukemia diagnosis and treatment may provide some guidance, additional research is needed to explore longer-term physical and psychosocial implications of leukemia and inform effective care plans to enhance quality of life in leukemia survivorship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation